State child maltreatment policies and disparities in substantiation: a study of state-administered child welfare systems in the U.S. - LaBrenz, Catherine (Child maltreatment, 2023)
Although several studies have examined child and family factors associated with substantiation, less research has explored the role of state child maltreatment policies in substantiating cases of alleged maltreatment. In parallel, there is growing pressure to reduce racial/ethnic disproportionality and disparities across the span of a child welfare case. We examined the relationship between state child maltreatment policies and substantiation, with child race/ethnicity as a moderator of this relationship. Data came from the 2019 National Child Abuse and Neglect Data System (NCANDS) and the State Child Abuse and Neglect (SCAN) Policy Database. Using a series of multi-level binary logistic models, we calculated the odds of substantiation based on child characteristics (e.g., child age, number of types of alleged maltreatment) and state policies (e.g., state definitions of maltreatment that include exposure to domestic violence, harsh punishment). Approximately 17% of the variance in substantiation occurs between states. Although we did not find a direct effect of state policy on substantiation, there were significant interaction terms, in that inclusion of exposure to domestic violence, harsh punishment, or educational neglect in state policy was more strongly associated with substantiation for children of color than white children. Implications for policy and research are explored.